Low-sintering medium microwave dielectric ceramic material and preparation method thereof
By using ZnO doped BaTi4O9 phase, modified dopant and glass phase in microwave dielectric ceramic materials, the sintering temperature is reduced to 990℃~1040℃, the problem of high sintering temperature of intermediary high Q materials is solved, and the ceramic materials are realized High dielectric performance and temperature stability.
Patent Information
- Application Number
- CN202411056201.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-02
AI Technical Summary
The sintering temperature of existing high-Q microwave dielectric ceramic materials is relatively high and difficult to reduce, which affects the production efficiency and cost of the materials.
BaZn2Ti4O11-0.07Ba4Ti13O30-based sintering block formed by ZnO doping the BaTi4O9 phase, and a modified dopant and glass phase additive were added during the sintering process to reduce the sintering temperature to 990°C to 1040°C to form a dense microwave dielectric ceramic material.
Effectively reduces the sintering temperature and improves the dielectric properties of ceramic materials, including dielectric constant (εr), Q value and insulation resistance (Rj), temperature coefficient (τf) and density, meeting the excellent intermediary high Q and temperature stability. performance.
Smart Images

Figure CN119143499A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microwave components, and in particular to a low-fired intermediate microwave dielectric ceramic material and a preparation method thereof. Background Art
[0002] Microwave high-Q capacitors have the characteristics of high Q value, low ESR, low ESL, and high series resonant frequency. They are often used in microwave communications, radar or satellite communication equipment as impedance matching, tuning, coupling, current isolation, dielectric resonators, bypasses and filters.
[0003] In the field of information and communication, modern mobile communication systems are developing towards miniaturization, integration and low cost, which has led to the development of multi-layer ceramic capacitors (MLCC) and low temperature co-fired ceramic (LTCC) technology. MLCC can effectively achieve device miniaturization and integration due to its multi-layer structure design. Combined with low temperature co-fired technology, the use of low melting point metals (copper or silver) with good conductivity as built-in electrodes can effectively reduce raw material costs and energy costs.
[0004] At present, microwave high-Q capacitors have serial products both at home and abroad. Foreign manufacturers are mainly ATC, TEMEX, DLI, etc., all of which have independently developed ceramic materials to support their products. Domestic manufacturers also have relatively mature serial products, but the ceramic materials supporting the products are imported from abroad, so the localization of ceramic materials supporting this series of products has been put on the agenda.
[0005] Generally speaking, the intermediate high-Q microwave dielectric ceramic material system can be selected from BaO-TiO2 and (Zr, Sn)TiO4 ceramics, or multi-system composite ceramic materials can be selected according to the mixed logarithmic law of composite dielectrics - Lichtenecker formula. The existing intermediate high-Q materials have high sintering temperatures, and the technical problem of reducing their sintering temperatures is becoming more urgent. Summary of the invention
[0006] The purpose of the present invention is to provide a low-fired intermediate microwave dielectric ceramic material and a preparation method thereof, to provide a way of thinking on how to reduce the sintering temperature, and to solve the problem that the sintering temperature of intermediate high-Q microwave dielectric materials is relatively high.
[0007] The present invention is achieved through the following technical solutions:
[0008] In one aspect, the present invention provides a low-fired medium microwave dielectric ceramic material, the microwave dielectric ceramic material comprising: a sintered block, a modifier and a glass phase;
[0009] The main crystalline phase chemical formula of the sintered block is BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30 ;
[0010] Adding a modified dopant into the sintered block, wherein the modified dopant comprises at least one of R2O3, Nb2O5, CaTiO3, MnCO3 and MgO, wherein R is La or Dy;
[0011] A glass phase additive is added into the glass phase, and the glass phase additive includes: ZnO, B2O3, Nd2O3 and BaCO3.
[0012] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the microwave dielectric ceramic material includes: by weight, 100 parts of sintered block, 3 parts to 7 parts of glass phase, and 5.3 parts to 15.4 parts of modified dopant.
[0013] Further, in the low-fired intermediate microwave dielectric ceramic material, the amount of ZnO in the glass phase additive is 36wt%; the amount of B2O3 is 42wt%; the amount of Nd2O3 is 5.4wt% to 14.8wt%; the amount of BaCO3 is 7.2wt% to 16.6wt% according to the mass percentage in the glass phase;
[0014] And / or, based on the mass parts of the sintered block, the amount of R2O3 in the modified dopant is 0.2 to 0.8 parts, wherein R is La or Dy; the amount of Nb2O5 is 0.3 to 0.9 parts; the amount of CaTiO3 is 4 to 11 parts; the amount of MnCO3 is 0.4 to 1.6 parts; and the amount of MgO is 0.4 to 1.1 parts.
[0015] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the sintered block is formed by ZnO-doped BaTi4O9 phase.
[0016] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the glass phase includes: BaO-ZnO-B2O3 glass, ZnO-B2O3-Nd2O3 glass and ZnO-B2O3-BaO-Nd2O3 glass.
[0017] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the preparation of the sintered block includes:
[0018] According to BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30Weigh the raw materials ZnO, BaCO3 and TiO2 in a molar ratio of 1:(5-6), ball mill for 6h-8h, dry at 100℃-150℃ and sieve, raise the temperature from room temperature to 1110℃-1160℃ at a rate of 3℃ / min-6℃ / min, and sinter for 2h-4h.
[0019] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the preparation of the glass phase includes:
[0020] BaO-ZnO-B2O3 glass, ZnO-B2O3-Nd2O3 glass and ZnO-B2O3-BaO-Nd2O3 glass are uniformly mixed in proportion and sintered at 650°C to 700°C for 2h to 4h.
[0021] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the dielectric property of the microwave dielectric ceramic material is ε r :30±4,tanδ≤5×10 -4 @1MHz, R j ≥10 5 MΩ, E b ≥8Kv / mm, α c :0±30ppm / ℃.
[0022] In a second aspect, the present invention also provides a method for preparing the above-mentioned low-fired intermediate microwave dielectric ceramic material, comprising:
[0023] The sintered block, the glass phase and the modified dopant are mixed in proportion, ground and dried, and then sieved to obtain the porcelain material;
[0024] Adding a binder to the porcelain material to granulate, and then dry-pressing after screening to obtain a ceramic green body;
[0025] After the ceramic green body is subjected to a debonding treatment, the temperature is raised from 450°C to 550°C to 990°C to 1040°C at a rate of 1°C / min to 6°C / min, sintered for 2h to 6h, and then cooled in the furnace to obtain the dielectric ceramic material.
[0026] Furthermore, in the preparation method of the low-fired intermediate microwave dielectric ceramic material, the grinding and drying conditions are as follows: grinding for 20h to 25h at a material-to-ball ratio of 1:(5-6), and then drying at 100°C to 150°C;
[0027] And / or, the amount of the binder added is 8wt% to 10wt% of the porcelain material;
[0028] And / or, the binder is paraffin;
[0029] And / or, the dry pressing condition is 10Mpa to 20Mpa, and the pressure is maintained for 20s to 40s;
[0030] And / or, the conditions for debonding are to increase the temperature from room temperature to 450° C. to 550° C. at a rate of 1° C. / min to 6° C. / min and then keep the temperature for 1 h to 3 h.
[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0032] The low-fired intermediate microwave dielectric ceramic material and the preparation method thereof provided by the present invention adopts ZnO doped BaTi4O9 phase to form BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30 The BaTi4O9 phase synthesis temperature was first lowered to about 1150℃, and then the modified dopant and glass phase additive were introduced to further synthesize the BaZn2Ti4O9 phase. 11 -0.07Ba4Ti 13 O 30 The base sintered block is cooled to obtain dense BaZn2Ti4O at 990℃~1040℃ 11 -0.07Ba4Ti 13 O 30 Based microwave dielectric ceramic materials.
[0033] The low-sintering medium microwave dielectric ceramic material and the preparation method thereof provided by the present invention reduce the sintering temperature to 990°C to 1040°C. The dielectric property of the microwave dielectric ceramic material is ε r :30±4,tanδ≤5×10 -4 @1MHz, R j ≥10 5 MΩ, E b ≥8Kv / mm, α c : 0±30ppm / ℃, excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0035] Figure 1 A flow chart of a method for preparing a low-fired intermediate microwave dielectric ceramic material provided by the present invention;
[0036] Figure 2 This is a scanning electron microscope (SEM) image of the low-fired intermediate microwave dielectric ceramic material prepared in Experimental Example 1 of the present invention in Example 2;
[0037] Figure 3 The X-ray diffraction pattern of the ceramic material prepared in Experimental Example 2 of the present invention against Comparative Example 1;
[0038] Figure 4 This is a scanning electron microscope (SEM) image of the ceramic material provided for Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0040] Generally speaking, the medium high-Q microwave dielectric ceramic material system can be selected from BaO-TiO2 and (Zr, Sn)TiO4 ceramics, or multi-system composite ceramic materials can be selected according to the mixed logarithmic law of composite dielectrics - Lichtenecker formula. In the existing related technologies, microwave ceramic dielectric materials use CaTiO3-LaAlO3 composite system as the main material, with B2O3, SiO2, MnO2 and V2O5 as sintering aids, which can reduce the sintering temperature to 1150℃~1200℃, and its microwave dielectric performance is ε r ≈43, Q f ≈45000GHz, τ f ≈0±5ppm / ℃. In the existing related technologies, microwave ceramic materials are used (BaZn 1 / 3 Ta 2 / 3 O3) 1-x ·(BaRO3) x The system is used as the main material, where R = Ti, Zn, Zr, and B2O3, SiO2, MnO2 and V2O5 are used as sintering aids. The sintering temperature can be reduced to 1560℃~1630℃, and its microwave dielectric property is ε r ≈30, Q f ≈(110000~160000)GHz, τ f ≈(0.5~9)ppm / ℃. The sintering temperature of existing intermediate high-Q materials is relatively high, and the technical problem of lowering their sintering temperature is becoming more urgent.
[0041] How to reduce the sintering temperature of ceramic materials has always been of great concern. In the existing related technologies, the low-temperature preparation method of zinc titanate-based microwave ceramics is based on (Zn 1-x M x)TiO3 system as the main material, where M = Ni, Co, the microwave dielectric ceramics prepared by sol-gel method can reduce the sintering temperature to 800℃, but the preparation process of this method is complicated, the quality control point is difficult to grasp, and it is not suitable for industrial production. 1-x Sr x TiO3 system is used as the main material, and BaCu (B2O5) is used as the composite phase, which can reduce the sintering temperature to 950℃, and the Q value is 146.7 (984MHz). 0.5 Re 0.5 ) x Bi 1-x W x V 1-x O4 system is used as the main material, where Re=La, Nd, Sm, Dy, Gd, and the sintering temperature is 800℃. Its microwave dielectric property is ε r ≈60~80, Q f ≈(6000~9000)GHz, τ f ≈(-175~138)ppm / ℃. In the existing related technologies, low-fired microwave ceramic materials use BaZrO3-Mg2SiO4 composite system as the main material, with Bi2O3, H3BO3, Li(OH), SiO2, MgO and ZnO as sintering aids, which can reduce the sintering temperature to 900℃~930℃, and its microwave dielectric performance is ε r ≈12-16, Q f ≈(30000~50000)GHz, TCC meets C0G specifications. In the existing related technologies, Ba-Co-V based low dielectric low firing microwave ceramic materials use Co 2+ Substituting Ba in Ba3(VO4)2 2+ The sintering temperature is as low as 900℃~950℃, and its microwave dielectric properties are Q f ≈(25318~54063)GHz, τ f ≈(14~23)ppm / ℃. In the existing related technology, microwave ceramics for low-fired, low-dielectric, high-Q and high-stability capacitors are made of Ca 0.9-y- z Sr 0.1 Mg y Mn z (Zr 0.96 Ti 0.02 Hf 0.02 ) m ·O 1+2m As the main material, with B2O3, SiO2, BaO and CuO as sintering aids, the sintering temperature is as low as 980℃±30℃, and its microwave dielectric property is εr ≈18-20, TCC meets C0G specifications. In these related technologies, although they have achieved technical breakthroughs in low-temperature sintering, the dielectric properties and microwave properties of ceramic materials cannot simultaneously meet the excellent properties of medium high Q and temperature stability. In this regard, the present invention provides the following technologies:
[0042] In one aspect, the present invention provides a low-fired medium microwave dielectric ceramic material, the microwave dielectric ceramic material comprising: a sintered block, a modifier and a glass phase;
[0043] The main crystalline phase chemical formula of the sintered block is BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30 ;
[0044] Adding a modified dopant into the sintered block, wherein the modified dopant comprises at least one of R2O3, Nb2O5, CaTiO3, MnCO3 and MgO, wherein R is La or Dy;
[0045] A glass phase additive is added into the glass phase, and the glass phase additive includes: ZnO, B2O3, Nd2O3 and BaCO3.
[0046] The low-fired intermediate microwave dielectric ceramic material provided by the present invention is BaZn2Ti4O9 formed by ZnO doping BaTi4O9 phase. 11 -0.07Ba4Ti 13 O 30 The BaTi4O9 phase synthesis temperature was first lowered to about 1150℃, and then the modified dopant and glass phase additive were introduced to further synthesize the BaZn2Ti4O9 phase. 11 -0.07Ba4Ti 13 O 30 The base sintered block is cooled to obtain dense BaZn2Ti4O at 990℃~1040℃ 11 -0.07Ba4Ti 13 O 30 Based microwave dielectric ceramic materials.
[0047] In the sintered block, BaTi4O9 dielectric ceramic material has excellent microwave dielectric properties. r ≈40, Q≈6000, τ f ≈0ppm / ℃, but the sintering temperature is relatively high, about 1250℃ or higher. The introduction of ZnO can reduce the sintering temperature on the one hand, and on the other hand, the BaZn2Ti4O9 phase formed by ZnO doping 11 -0.07Ba4Ti 13 O 30The base sintered block also provides the prerequisite for the high Q performance of the porcelain material.
[0048] In the glass phase, after the BaTi4O9 phase is doped with ZnO, the sintering temperature has been reduced to about 1150℃, but it is far from meeting the requirements of low-temperature sintering. By adding glass phase additives such as BaO, ZnO, Nd2O3 and BaCO3, the synthesis temperatures of BaO-ZnO-B2O3 glass, ZnO-B2O3-Nd2O3 glass, ZnO-B2O3-BaO-Nd2O3 glass, etc. are all lower than 800℃. The addition of glass phase additives will effectively reduce the sintering temperature of ceramic materials to 990℃-1040℃.
[0049] In the modified dopant, trace amounts of La 3+ and Dy 3+ It can effectively adjust the charge balance of ceramic materials to reduce the oxygen vacancy concentration, which is beneficial to reduce dielectric loss and increase Q value; at the same time, La2O3 can play a role in grain refinement, which is beneficial to reduce grain size and enhance the density of ceramic materials, which has a positive impact on improving product reliability. 2+ and Nb 5+ After introduction, they replaced Ba 2+ Bit and Ti 4+ The position causes lattice distortion, which is beneficial to adjust the temperature coefficient of ceramic materials. On the other hand, the introduction of Nb2O5 and BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30 The combination of the base sintered block forms a trace amount of ZnNb2O6 phase, which has a very positive effect on improving the Q value of ceramic materials. Since the oxygen in the lattice of BaO-TiO2 series ceramic materials is easy to escape during high-temperature sintering, a large number of positively charged oxygen vacancies and free electrons are left inside the lattice, and the free electrons are easily absorbed by the Ti in the lattice. 4+ Ti 3+ (or Ti 4+ ·e), which leads to a decrease in the insulation resistance of dielectric ceramics. The introduction of MnCO3 and MgO can effectively inhibit the 4+ Reduced to Ti 3+ , improve the insulation properties of ceramic materials.
[0050] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the microwave dielectric ceramic material includes: by weight, 100 parts of sintered block, 3 parts to 7 parts of glass phase, and 5.3 parts to 15.4 parts of modified dopant.
[0051] The amount of the glass phase added to the microwave dielectric ceramic material is 3 to 7 parts, which can be 3, 4, 5, 6, 7, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0052] The modified dopant is added to the microwave dielectric ceramic material in an amount of 5.3 parts, 5.5 parts, 5.7 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 15.4 parts, etc., but is not limited to the listed values, and other values not listed in the range are also applicable. Further, in the low-fired intermediate microwave dielectric ceramic material, the amount of ZnO in the glass phase additive is 36wt% according to the mass percentage in the glass phase; the amount of B2O3 is 42wt%;
[0053] The amount of Nd2O3 is 5.4wt% to 14.8wt%, and can be 5.4wt%, 5.8wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 14.8wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable;
[0054] The amount of BaCO3 is 7.2wt% to 16.6wt%, and can be 7.2wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 15wt%, 15.5wt%, 16wt%, 16.5wt%, 16.6wt% and the like, but is not limited to the listed values, and other values not listed within the range are equally applicable.
[0055] Further, in the low-fired intermediate microwave dielectric ceramic material, the amount of R2O3 in the modified dopant is 0.2 to 0.8 parts, and can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc., etc., but is not limited to the listed values, and other values not listed within the range are also applicable, wherein R is La, Dy;
[0056] The amount of Nb2O5 is 0.3 to 0.9 parts, and can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, etc., but is not limited to the values listed, and other values not listed within the range are also applicable;
[0057] The amount of CaTiO3 is 4 to 11 parts, which can be 4, 5, 6, 7, 8, 9, 10, 11, etc., but is not limited to the values listed, and other values not listed within the range are also applicable;
[0058] The amount of MnCO3 is 0.4 to 1.6 parts, which can be 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, etc., but is not limited to the values listed, and other values not listed within the range are also applicable;
[0059] The amount of MgO is 0.4 to 1.1 parts, and can be 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0060] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the sintered block is formed by ZnO-doped BaTi4O9 phase.
[0061] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the glass phase includes: BaO-ZnO-B2O3 glass, ZnO-B2O3-Nd2O3 glass and ZnO-B2O3-BaO-Nd2O3 glass.
[0062] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the preparation of the sintered block includes:
[0063] According to BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30The raw materials ZnO, BaCO3 and TiO2 are weighed in a molar ratio of 1:(5-6) (the material-ball ratio can be 1:5, 1:5.2, 1:5.5, 1:5.8, 1:6, etc.), and ball milled for 6h-8h (the ball milling time is 6h, 6.5h, 7h, 7.5h, 8h, etc.), and then at 100℃-150℃ (the temperature can be 100℃, 110℃, 120℃, 125℃, 130℃, 140℃, 150℃ The temperature is raised from room temperature to 1110°C to 1170°C (the temperature may be 1100°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, etc.) at a rate of 3°C / min to 6°C / min (the rate may be 3°C / min, 4°C / min, 5°C / min, 6°C / min, etc.), and then sintered for 2h to 4h (the time may be 2h, 2.5h, 3h, 4h, etc.).
[0064] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the preparation of the glass phase includes:
[0065] After uniformly mixing BaO-ZnO-B2O3 glass, ZnO-B2O3-Nd2O3 glass and ZnO-B2O3-BaO-Nd2O3 glass in proportion, sinter at 650℃~700℃ (the temperature can be 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, etc.) for 2h~4h (the time can be 2h, 2.5h, 3h, 4h, etc.).
[0066] Furthermore, in the low-fired intermediate microwave dielectric ceramic material, the dielectric property of the microwave dielectric ceramic material is ε r :30±4,tanδ≤5×10 -4 @1MHz, R j ≥10 5 MΩ, E b ≥8Kv / mm, α c :0±30ppm / ℃.
[0067] Second, please refer to Figure 1 The present invention also provides a method for preparing the above-mentioned low-fired intermediate microwave dielectric ceramic material, comprising:
[0068] The sintered block, the glass phase and the modified dopant are mixed in proportion, ground and dried, and then sieved to obtain the porcelain material;
[0069] Adding a binder to the porcelain material to granulate, and then dry-pressing after screening to obtain a ceramic green body;
[0070] After the ceramic green body is subjected to a debonding treatment, the temperature is raised from 450°C to 550°C (the temperature may be 450°C, 470°C, 490°C, 500°C, 520°C, 550°C, etc.) to 990°C to 1040°C (the temperature may be 990°C, 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, etc.) at a rate of 1°C to 6°C / min (the rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, etc.), sintered for 2h to 6h (the time may be 2h, 2.5h, 3h, 4h, 5h, 6h, etc.), and then cooled in the furnace to obtain the dielectric ceramic material.
[0071] Further, in the preparation method of the low-fired intermediate microwave dielectric ceramic material, the grinding and drying conditions are as follows: grinding for 20h to 25h (ball milling time is 20h, 21h, 22h, 23h, 24h, 25h, etc.) at a material-ball ratio of 1: (5-6) (the material-ball ratio can be 1:5, 1:5.2, 1:5.5, 1:5.8, 1:6, etc.), and then drying at 100°C to 150°C (the temperature can be 100°C, 110°C, 120°C, 125°C, 130°C, 140°C, 150°C, etc.);
[0072] And / or, the amount of the binder added is 8wt% to 10wt% of the porcelain material, which can be 8wt%, 8wt%, 9wt%, 9.5wt%, 10wt%, etc.;
[0073] And / or, the binder is paraffin;
[0074] And / or, the conditions for dry pressing are 10Mpa to 20Mpa, which may be 10Mpa, 12Mpa, 15Mpa, 17Mpa, 20Mpa, etc.; the pressure is maintained for 20s to 40s, which may be 20s, 25s, 30s, 35s, 40s, etc.;
[0075] And / or, the conditions for debonding are to increase the temperature from room temperature to 450°C to 550°C (the temperature may be 450°C, 470°C, 490°C, 500°C, 520°C, 550°C, etc.) at a rate of 1°C / min to 6°C / min (the rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, etc.), and then keep warm for 1h to 3h (the time may be 1h, 2h, 2.5h, 3h, etc.).
[0076] In order to further illustrate the present invention, a low-fired intermediate microwave dielectric ceramic material and a preparation method thereof provided by the present invention are described below in combination with examples. However, it should be understood that these examples are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples.
[0077] Example 1
[0078] The method for preparing the low-fired intermediate microwave dielectric ceramic material provided in this embodiment comprises the following steps:
[0079] (1) Sintered block preparation: According to BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30 The raw materials ZnO, BaCO3 and TiO2 were weighed in a molar ratio of 1:5.5, ball-milled for 7 hours at a material-ball ratio of 1:5.5, dried at 120°C and sieved, and the temperature was raised from room temperature to 1150°C at a rate of 5°C / min, and sintered for 2 hours to obtain a sintered block.
[0080] (2) Preparation of glass phase frit: BaO-ZnO-B2O3 glass, ZnO-B2O3-Nd2O3 glass and ZnO-B2O3-BaO-Nd2O3 glass were uniformly mixed in proportion, sintered at 670°C for 2 h and cooled in the furnace to obtain a glass phase frit. Among them, according to the glass phase formula ratio, 20 g of ZnO; 23 g of B2O3; 5 g of Nd2O3; and 7 g of BaCO3 were weighed.
[0081] (3) Preparation of dielectric ceramics: 20 g of sintered block, 0.80 g of glass phase melt and modified dopant were mixed in proportion, ball milled for 22 h at a material-ball ratio of 1:5.5, dried in an oven at 120°C and sieved to obtain a ceramic material; wherein, based on the calculation of 20 g of sintered block, the modified dopant contained 0.04 g of La2O3, 1.6 g of CaTiO3, 0.10 g of Nb2O5, 0.02 g of MnCO3 and 0.014 g of MgO.
[0082] The porcelain material was granulated with 9wt% paraffin as a binder, sieved and dry-pressed to obtain a ceramic green body with a molding pressure of 15Mpa and maintained at pressure for 30 seconds; the temperature was raised from room temperature to 500℃ at a rate of 2.5℃ / min for 2 hours to remove adhesive, and then the temperature was raised from 500℃ to 1010℃ at a rate of 5℃ / min, sintered for 4 hours, and then cooled in the furnace to obtain a dielectric ceramic sample.
[0083] Example 2
[0084] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 1, except that: the mass of La2O3 in the modified dopant is 0.10g, calculated in 20g of the sintered block.
[0085] Example 3
[0086] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 1, except that: the mass of La2O3 in the modified dopant is 0.16g, calculated in 20g of the sintered block.
[0087] Example 4
[0088] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that: the mass of CaTiO3 in the modified dopant is 0.80g, calculated in 20g of the sintered block.
[0089] Example 5
[0090] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that: the mass of CaTiO3 in the modified dopant is 2.2g, calculated in 20g of the sintered block; and the sintering temperature is 1020°C.
[0091] Example 6
[0092] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that: the mass of Nb2O5 in the modified dopant is 0.06g, calculated in 20g of the sintered block.
[0093] Example 7
[0094] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that: the mass of Nb2O5 in the modified dopant is 0.18g, calculated in 20g of the sintered block.
[0095] Example 8
[0096] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that: the mass of MnCO3 in the modified dopant is 0.008g, calculated in 20g of the sintered block.
[0097] Example 9
[0098] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to Example 2, except that: the mass of MnCO3 in the modified dopant is 0.032g, calculated in 20g of the sintered block.
[0099] Example 10
[0100] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that: the mass of MgO in the modified dopant is 0.008 g, calculated in 20 g of the sintered block.
[0101] Embodiment 11
[0102] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that: the mass of MgO in the modified dopant is 0.022 g, calculated in 20 g of the sintered block.
[0103] Example 12
[0104] The method for preparing the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specific to that of Embodiment 2, except that the mass of the glass phase frit is 0.40 g and the sintering temperature is 1020°C.
[0105] Example 13
[0106] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that: the mass of the glass phase frit is 1.4 g; and the sintering temperature is 1000°C.
[0107] Embodiment 14
[0108] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that the mass of Nd2O3 in the glass additive is 3g.
[0109] Embodiment 15
[0110] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to Example 2, except that the mass of Nd2O3 in the glass additive is 8g.
[0111] Example 16
[0112] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that the mass of BaCO3 in the glass additive is 4g.
[0113] Embodiment 17
[0114] The preparation method of the low-fired intermediate microwave dielectric ceramic material provided in this embodiment is specifically referred to in Example 2, except that the mass of BaCO3 in the glass additive is 10g.
[0115] The formula comparison of Examples 1-17 is shown in Table 1:
[0116] Table 1
[0117]
[0118]
[0119] The performance of the low-fired intermediate microwave dielectric ceramic materials obtained in Examples 1-17 was tested, and the results are shown in Table 2:
[0120] Table 2
[0121]
[0122] From the above table, it can be seen that the dielectric properties of the low-fired intermediate microwave dielectric ceramic material prepared in the embodiment of the present invention are, ε r :30±4,tanδ≤5×10 -4 @1MHz, R j ≥10 5 MΩ,,E b ≥8Kv / mm, α c :0±30ppm / ℃. The performance of microwave dielectric ceramic materials is stable and can be used to manufacture microwave components such as resonators, filters, dielectric ceramic substrates, antennas, etc.
[0123] Comparative Example 1
[0124] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically referred to Example 2, except that: the amount of the modified dopant added is 0 g, the mass of the glass phase melt is 0 g; and the sintering temperature is 1150°C.
[0125] Comparative Example 2
[0126] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically referred to Example 2, except that: the amount of the modified dopant added is 0 g, the mass of the glass phase frit is 0.80 g; and the sintering temperature is 1020°C.
[0127] Comparative Example 3
[0128] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that the mass of La2O3 in the modified dopant is 0g, calculated in 20g of the sintered block.
[0129] Comparative Example 4
[0130] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that: the mass of La2O3 in the modified dopant is 0.22g, calculated in 20g of the sintered block.
[0131] Comparative Example 5
[0132] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that the mass of CaTiO3 in the modified dopant is 0 g, calculated in 20 g of the sintered block.
[0133] Comparative Example 6
[0134] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that: the mass of CaTiO3 in the modified dopant is 3.0 g, calculated in 20 g of the sintered block; and the sintering temperature is 1030°C.
[0135] Comparative Example 7
[0136] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that: the mass of Nb2O5 in the modified dopant is 0g, calculated in a 20g sintered block; and the sintering temperature is 1020°C.
[0137] Comparative Example 8
[0138] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically the same as that in Example 2, except that: the mass of Nb2O5 in the modified dopant is 0.24g, calculated in 20g of the sintered block; and the sintering temperature is 1000°C.
[0139] Comparative Example 9
[0140] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that: the mass of MnCO3 in the modified dopant is 0g, calculated in 20g of the sintered block.
[0141] Comparative Example 10
[0142] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that: the mass of MnCO3 in the modified dopant is 0.04g, calculated in 20g of the sintered block.
[0143] Comparative Example 11
[0144] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that: the mass of MgO in the modified dopant is 0 g, calculated in 20 g of the sintered block.
[0145] Comparative Example 12
[0146] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically similar to that in Example 2, except that: the mass of MgO in the modified dopant is 0.028 g, calculated in 20 g of the sintered block.
[0147] Comparative Example 13
[0148] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically referred to Example 2, except that the mass of the glass phase frit is 0 g.
[0149] Comparative Example 14
[0150] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically referred to Example 2, except that: the mass of the glass phase frit is 1.6 g; and the sintering temperature is 960°C.
[0151] Comparative Example 15
[0152] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically referred to Example 2, except that: the mass of Nd2O3 in the glass additive is 0g; and the sintering temperature is 1030°C.
[0153] Comparative Example 16
[0154] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically the same as that in Example 2, except that the mass of Nd2O3 in the glass additive is 12 g and the sintering temperature is 1000°C.
[0155] Comparative Example 17
[0156] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically referred to Example 2, except that the mass of BaCO3 in the glass additive is 0g.
[0157] Comparative Example 18
[0158] The preparation method of the microwave dielectric ceramic material provided in this comparative example is specifically referred to Example 2, except that: the mass of BaCO3 in the glass additive is 15g; and the sintering temperature is 1050°C.
[0159] The formula comparison of comparative examples 1-18 is shown in Table 3:
[0160]
[0161]
[0162] The performance of the microwave dielectric ceramic materials obtained in Comparative Examples 1-18 was tested, and the results are shown in Table 4:
[0163]
[0164]
[0165] As can be seen from the table above, the comparative examples 1-18 respectively change the contents of La2O3, CaTiO3, Nb2O5, MnCO3 and MgO in the dopant, the glass phase content, and the contents of ZnO, B2O3, Nd2O3, BaCO3 in the glass additives and the sintering temperature to study the effects on the performance of the microwave dielectric ceramic material. As can be seen from the results in the table above, the performance of the microwave dielectric ceramic material obtained in the comparative example is lower than that of the low-fired medium microwave dielectric ceramic material obtained in the embodiment of the present invention.
[0166] Test Example 1
[0167] The surface of the low-fired intermediate microwave dielectric ceramic material prepared in Example 2 was characterized by SEM. Figure 2 .
[0168] from Figure 2 It can be seen that the ceramic body of the ceramic material is composed of grains of 1 to 2 um, and the grains are evenly distributed.
[0169] Test Example 2
[0170] The surface of the microwave dielectric ceramic material prepared in Comparative Example 1 was characterized by X-ray and SEM. Figure 3 and Figure 4 .
[0171] The raw material of the ceramic material only contains sintered blocks. From the X-ray diffraction diagram, it can be seen that the sintered blocks are composed of BaZn2Ti4O 11 Phase and Ba4Ti 13 O 30 Phase composition. From the SEM image, it can be seen that the porcelain body is composed of small grains with a diameter of 2um and long rod-shaped grains with a diameter of 12um. The distribution position and grain size of the grains are uneven.
[0172] Comparing the SEM images of the ceramic bodies of Example 2 and Comparative Example 1, the grain refinement effect of the ceramic body of the ceramic material in Example 2 is obvious.
[0173] Test Example 3
[0174] The microwave performance tests were performed on the low-fired intermediate microwave dielectric ceramic material prepared in Example 2 and the microwave dielectric ceramic materials prepared in Comparative Examples 1 and 2, and the results are shown in Table 5:
[0175] Table 5
[0176]
[0177]
[0178] It can be seen from the above table that the low-fired intermediate microwave dielectric ceramic material provided by Example 2 of the present invention has a higher Q value than that of Comparative Examples 1 and 2.
[0179] Experimental Example 4
[0180] The low-fired intermediate microwave dielectric ceramic material obtained in Example 2 was made into a chip-type multilayer ceramic dielectric capacitor (MLCC) for performance testing and compared with imported products. The results are shown in Table 6:
[0181] Table 6
[0182]
[0183] It can be seen from the above table that the chip-type multilayer ceramic dielectric capacitor made of the low-fired intermediate microwave dielectric ceramic material provided by the present invention has comparable performance to imported products in terms of dielectric loss, insulation resistance, temperature coefficient and S21 coefficient, and is significantly superior to imported products in terms of ESR and Q value, with better performance.
[0184] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A low-fired intermediate microwave dielectric ceramic material, characterized in that: The microwave dielectric ceramic material comprises: a sintered block, a modifier and a glass phase; The main crystalline phase chemical formula of the sintered block is BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30 ; Adding a modified dopant into the sintered block, wherein the modified dopant comprises at least one of R2O3, Nb2O5, CaTiO3, MnCO3 and MgO, wherein R is La or Dy; A glass phase additive is added into the glass phase, and the glass phase additive includes: ZnO, B2O3, Nd2O3 and BaCO3.
2. A low-fired intermediate microwave dielectric ceramic material according to claim 1, characterized in that: The microwave dielectric ceramic material comprises: by weight, 100 parts of sintered block, 3 parts to 7 parts of glass phase, and 5.3 parts to 15.4 parts of modified dopant.
3. The low-fired intermediate microwave dielectric ceramic material according to claim 1, characterized in that: According to the mass percentage in the glass phase, the amount of ZnO in the glass phase additive is 36wt%; the amount of B2O3 is 42wt%; the amount of Nd2O3 is 5.4wt% to 14.8wt%; the amount of BaCO3 is 7.2wt% to 16.6wt%; And / or, based on the mass parts of the sintered block, the amount of R2O3 in the modified dopant is 0.2 to 0.8 parts, wherein R is La or Dy; the amount of Nb2O5 is 0.3 to 0.9 parts; the amount of CaTiO3 is 4 to 11 parts; the amount of MnCO3 is 0.4 to 1.6 parts; and the amount of MgO is 0.4 to 1.1 parts.
4. The low-fired intermediate microwave dielectric ceramic material according to claim 1, characterized in that: The sintered mass is formed of a ZnO-doped BaTi4O9 phase.
5. The low-fired intermediate microwave dielectric ceramic material according to claim 1, characterized in that: The glass phase includes: BaO-ZnO-B2O3 glass, ZnO-B2O3-Nd2O3 glass and ZnO-B2O3-BaO-Nd2O3 glass.
6. A low-fired intermediate microwave dielectric ceramic material according to any one of claims 1 to 5, characterized in that: The preparation of the sintered block comprises: According to BaZn2Ti4O 11 -0.07Ba4Ti 13 O 30 Weigh the raw materials ZnO, BaCO3 and TiO2 in a molar ratio of 1:(5-6), ball mill for 6h-8h, dry at 100℃-150℃ and sieve, raise the temperature from room temperature to 1110℃-1170℃ at a rate of 3℃ / min-6℃ / min, and sinter for 2h-4h.
7. A low-fired intermediate microwave dielectric ceramic material according to any one of claims 1 to 5, characterized in that: The preparation of the glass phase comprises: BaO-ZnO-B2O3 glass, ZnO-B2O3-Nd2O3 glass and ZnO-B2O3-BaO-Nd2O3 glass are uniformly mixed in proportion and sintered at 650°C to 700°C for 2h to 4h.
8. A low-fired intermediate microwave dielectric ceramic material according to any one of claims 1 to 5, characterized in that: The dielectric property of the microwave dielectric ceramic material is ε r :30±4,tanδ≤5×10 -4 @1MHz, R j ≥10 5 MΩ, E b ≥8Kv / mm, α c :0±30ppm / ℃.
9. A method for preparing a low-fired intermediate microwave dielectric ceramic material according to any one of claims 1 to 8, characterized in that: include: The sintered block, the glass phase and the modified dopant are mixed in proportion, ground and dried, and then sieved to obtain the porcelain material; Adding a binder to the porcelain material to granulate, and then dry-pressing after screening to obtain a ceramic green body; After the ceramic green body is subjected to a debonding treatment, the temperature is raised from 450°C to 550°C to 990°C to 1040°C at a rate of 1°C / min to 6°C / min, sintered for 2h to 6h, and then cooled in the furnace to obtain the dielectric ceramic material.
10. The method for preparing a low-fired intermediate microwave dielectric ceramic material according to claim 9, characterized in that: The conditions for grinding and drying are: grinding for 20h to 25h at a material-to-ball ratio of 1:(5-6), and then drying at 100°C to 150°C; And / or, the amount of the binder added is 8wt% to 10wt% of the porcelain material; And / or, the binder is paraffin; And / or, the dry pressing condition is 10Mpa to 20Mpa, and the pressure is maintained for 20s to 40s; And / or, the conditions for debonding are to increase the temperature from room temperature to 450° C. to 550° C. at a rate of 1° C. / min to 6° C. / min and then keep the temperature for 1 h to 3 h.
Citation Information
Patent Citations
Low-temperature sintered microwave medium ceramic material and preparation method thereof
CN101613200A
Zinc barium titanate system ceramic low temperature sintering material and preparation method thereof
CN103408299A
Low-temperature sintered microwave ceramic material and preparation method thereof
CN103420670A
Medium-dielectric-constant low-temperature co-fired microwave dielectric ceramic substrate material and preparation method thereof
CN117069490A
Low-temperature sintered high-stability microwave dielectric material as well as preparation method and application thereof
CN118039356A
Cited By
Low-temperature rare earth pyrochlore microwave dielectric ceramic material and preparation method thereof
CN119930287A
